On the influence of infrastructure availability on companies decisions toward modal shift and relocation of falicities - Rebecca Wehrle; Johannes Gast; Marcus Wiens; Frank Schultmann (Transportation Research Interdisciplinary Perspectives, 2023)
Purpose: Reduced availability of transport infrastructure affects highly dependent global supply chains (SCs), leading to modal shifts in the short term. Since relocation decisions of facilities may result in the long term, this paper evaluates companies’ business decisions in reaction to availability reductions of inland waterway transport (IWT). Methodology: A transport model evaluates the impact of reduced infrastructure availability through heuristic optimization based on the Traveling Purchaser Problem. The resulting increase in operational costs is used to assess the probability of relocating facilities based on a Facility Location Problem (FLP) which enables deriving the benefit from infrastructure conditions. Findings: The study identifies critical thresholds for infrastructure availability that affect companies’ relocation decisions regarding the maintenance of public infrastructure. The case study exhibits actual critical infrastructure assets. Practical implications: Insights into the decisive consequences of companies’ decisions are given, and awareness of the relevance of infrastructure investments on local areas’ attractiveness is raised. The results imply considering public infrastructure investments in maintenance for private business locations. Originality: The paper highlights a new way to sustain local industries and connects short-term agility and long-term resilience with companies’ decisions and the exogenous factor infrastructure availability. The applied use case focuses on the barely studied waterway infrastructure that gains importance in light of sustainability and climate change.